Effectivity of Virtual Field Trip-Based Learning on Elementary School Students' Scientific Literacy - Marpian; Wahyu Sopandi; Yulianti Fitriani (MANDAILING GLOBAL EDUKASIA, 2026)
Developing scientific literacy in elementary education is critical, yet traditional classroom methods often struggle to foster high engagement and contextual understanding, particularly in resource-limited settings. While digital interventions are rising, the specific efficacy of virtual field trips (VFT) in transformative science learning remains insufficiently explored. This study aims to examine the effect of virtual field trip-based learning on elementary school students' scientific literacy. Utilizing a quantitative quasi-experimental design, this study involved 60 fifth-grade students, divided equally into an experimental class (utilizing VFT) and a control class (traditional instruction). Data were collected through a structured scientific literacy questionnaire and analyzed using both descriptive and inferential statistics, specifically paired and independent sample t-tests. The findings indicate that VFT-based learning exerts a positive and highly significant effect on students' scientific literacy. The experimental group exhibited a remarkable increase in mean scientific literacy scores, soaring from 60.63 (low category) pre-treatment to 92.18 (very high category) post-treatment. Conversely, the control group only achieved a post-test mean of 67.16 (low category), demonstrating that VFT integration yields significantly superior outcomes compared to conventional methods (p < 0.05). Consequently, VFT-based learning serves as a potent pedagogical alternative to mitigate low scientific literacy. Beyond individual score gains, these insights offer a scalable framework for curriculum developers to integrate immersive digital technologies into early science education, bridging the gap between abstract scientific concepts and real-world phenomena.